Protocol for a feasibility study and process evaluation of a psychosocially modelled diabetes education programme for young people with type 1 diabetes: the Youth Empowerment Skills (YES) programme - Nick Sevdalis; Khalida Ismail; Tayana Soukup; Trevor Murrells; Dulmini Kariyawasam; Stephen Thomas; Judith Parsons; Angus Forbes; Rita Forde; Maria Baldellou Lopez; Marie Jones; Martha Ford-Adams; et al. (BMJ Open)
Introduction Adolescence is a challenging period for young people with type 1 diabetes, associated with worsening glycaemia and care disengagement. Educational interventions in this period tend to focus on diabetes-specific skills, with less emphasis on the psychosocial challenges associated with diabetes experienced by young people. To address this limitation, we codesigned with young people a psychosocially modelled programme of diabetes education, named ‘Youth Empowerment Skills’ (YES). The programme aims to facilitate a positive adaptation to life with diabetes and engagement with diabetes care through peer-based learning, immersive simulations and support from an outreach youth worker. Here, we present a protocol for a feasibility study of the YES programme.Methods and analysis The study was designed following the Medical Research Council Complex Intervention Evaluation Framework to: test the feasibility (acceptance, implementability, recruitment and completion) of the YES programme; and estimate its efficacy in relation to metabolic and psychosocial outcomes. The study will take place in diabetes centres serving socioculturally diverse populations. We will conduct a feasibility randomised controlled trial (waiting-list design) with integrated process evaluation. Fifty young people with type 1 diabetes (aged 14–19 years) will be randomly allocated to either the YES intervention or a waiting-list control. Randomisation acceptability will be assessed with provision for a preference allocation. Outcomes will be evaluated at 6 months, at which point the waiting list participants will be exposed to the YES programme with further follow-up to 12 months. A simultaneous process evaluation will use a mixed-methods approach collecting qualitative and quantitative data. Study findings will be used to optimise the intervention components, outcome measures and recruitment methods to inform a subsequent definitive trial.Ethics and dissemination The protocol has ethical approval from the UK Health Research Authority (approval IRAS project ID: 279877). Findings will be disseminated in multiple formats for lay and professional audiences.Protocol date and version 7 April 2021, V.1.1.Trial registration number NCT04670198.